The Effect of Finger-Holding on Anxiety Levels in Patients Undergoing Preoperative Preparation For a Cesarean Section at Columbia Asia Semarang Surgical Hospital - Hayu Rismawati; Menik Kustriyani (Hippocratica : Journal of Modern Medicine and Healthcare Practice, 2026)
This empirical case study evaluated the clinical efficacy of finger holding relaxation therapy as an autonomous, non pharmacological nursing intervention to alleviate preoperative anxiety in maternal patients undergoing Cesarean section preparations. Conducted at Columbia Asia Semarang Surgical Hospital in May 2026, the study utilized a descriptive one group pretest posttest design involving five homogenous maternal candidates selected through purposive sampling. The clinical protocol required structured manual digital compression administered for fifteen minutes daily over two consecutive days in a quiet, controlled environment, with anxiety levels quantified using the standardized Hamilton Anxiety Rating Scale. The baseline metrics revealed a uniform distribution of moderate anxiety across all participants, which was successfully down regulated to mild anxiety post intervention, yielding a meaningful reduction in systemic emotional distress. The psychophysiological mechanism involves peripheral nerve stimulation that triggers parasympathetic activation, thereby reducing adrenaline and cortisol production while providing an effective somatosensory distraction from procedural fear. Adherence to a strict Standard Operating Procedure preserved high internal validity, confirming this technique is safe, reproducible, and highly effective for optimizing preoperative readiness.